La précarité, une norme imposée aux jeunes femmes des classes populaires rurales - Perrine Agnoux (La Nouvelle Revue du Travail, 2023)
This article highlights injunctions made upon young women from rural working classes when entering the labor market and the consequences on their professional trajectories. Based on an ethnographic survey of women holding a vocational baccalauréat certificate in the medical-social sector, it shows that not all young women have the family support required to conform to the model of the young worker, as defined by employment policies and institutions, particularly necessary in rural areas. Girls from precarious parts of society, whose experience of independence is brutal, struggle to find stability because of their discrepancies with this model, while the normalization of precarity favors the exploitation of those who benefit from parental support when entering the labor market.